Biomaterials : an introduction - Park, Joon.; Lakes, R. S. ([S.l.] : Springer, 2010)
With sixty years of combined experience, the authors of this extensively revised book have learned to emphasize the fundamental materials science, structure-property relationships, and biological responses as a foundation for a wide array of biomaterials applications. This edition includes a new chapter on tissue engineering and regenerative medicine, approximately 1900 references to additional reading, extensive tutorial materials on new developments in spinal implants and fixation techniques and theory. It also offers systematic coverage of orthopedic implants, and expanded treatment of ceramic materials and implants.